The Development of an E-learning Lessons Principles of Advertising and Public Relations for Undergraduate Student - Kukkong, Prajak (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This study aims to 1) develop e-learning lessons Principles of advertising and public relations principles to be effective according to criteria studying with e-learning lessons. The population used in this study is 18 1st-year undergraduate students in Communication Arts Kamphaeng Phet Rajabhat University who enrolled in the semester of 1/2020. The tools used in the study consisted of 1) e-learning lessons on Principles of advertising and public relations principles, 2) Learning achievement test on Principles of Advertising and Public Relations, and 3) Satisfaction Questionnaire on e-learning lessons Principles of Advertising and Public Relations. Data were analyzed using percentages, mean, standard deviation, and t-test. The study indicated that 1) The efficiency of e-learning lessons on Principles of Advertising and Public Relations was 85.90/80.80 which meets the standard criteria, 2) Learning achievement of post-learning from e-learning lessons on Principles of advertising and public relations was higher than pre-learning with statically significant at the level of .05., and 3) Satisfaction of 1st year undergraduate students in Communication Arts, Kamphaeng Phet Rajabhat University who studied with e-learning lessons on Principles of Advertising and Public relations in the overall was at the highest level (mean=4.57, SD=0.71).